PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV DI SD NEGERI 143 PEKANBARU - Wita Warnis; Alpusari, Mahmud; Antosa, Zariul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education is a planned effort to develop students' potential optimally. However, based on the results of observations and interviews at SD Negeri 143 Pekanbaru, student learning outcomes in the subject of science are still relatively low, which is caused by the lack of student activity and the use of learning methods that are still centered on the teacher. This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the science learning outcomes of fourth grade students. This study uses a quantitative approach with an experimental design involving two classes, namely the experimental class using the PBL model and the control class using the expository method. Data collection was carried out through pretests and posttests, then analyzed using descriptive and inferential statistical tests, including normality tests, homogeneity tests, independent sample t-tests, and N-Gain tests with the help of SPSS version 21. The results showed that the average posttest score of the experimental class was 81.00 higher than the control class at 63.50. The results of the t-test showed a significance value of 0.000 <0.05, which means there is a significant effect of the use of the PBL model on student learning outcomes. In addition, the N-Gain test results showed that the increase in learning outcomes in the experimental class was in the medium category (0.69), while the control class was in the low category (0.27). Thus, the Problem Based Learning model was proven to be more effective in improving students' science learning outcomes than the expository method.